Composite coating as well as preparation method and application thereof

By combining epoxy resin, end-carboxylic liquid nitrile rubber, polyurethane prepolymer, hydrophobic material and hydrogen resistance material in the composite coating, a ternary interpenetrating network structure with high cross-link density is solved, and the problem of poor hydrogen resistance performance of the existing hydrogen resistance coating is significantly improved and hydrogen embrittlement is suppressed.

CN119859457AActive Publication Date: 2025-04-22CHINA PETROLEUM & CHEMICAL CORP +2

Patent Information

Application Number
CN202311367055.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-04-22
Estimated Expiration
2043-10-20

AI Technical Summary

Technical Problem

The existing hydrogen-resistance coating has poor hydrogen resistance performance in a hydrogen-facing environment and cannot effectively inhibit the occurrence of hydrogen embrittlement.

Method used

A composite coating is used, and its raw materials include epoxy resin, end-carboxylic liquid nitrile rubber, polyurethane prepolymer, hydrophobic material and hydrogen resistance material. By regulating the raw material ratio and vacuum stirring conditions, a ternary interpenetrating network structure with high cross-linking density is formed to improve hydrogen resistance performance.

Benefits of technology

It significantly improves the hydrogen resistance performance of the coating, reduces the hydrogen permeability current density, effectively suppresses the occurrence of metal hydrogen embrittlement, and extends the service life and reliability of metal components of hydrogen-fast equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004504695780000261
    Figure BDA0004504695780000261
  • Figure BDA0004504695780000271
    Figure BDA0004504695780000271
Patent Text Reader

Abstract

The invention relates to the field of composite materials, and discloses a composite coating as well as a preparation method and application thereof, and raw materials for preparing the composite coating comprise epoxy resin, carboxyl-terminated liquid nitrile rubber, a polyurethane prepolymer, a hydrophobic material and a hydrogen-resistant material. The method for preparing the composite coating comprises the following steps: (1) mixing epoxy resin, carboxyl-terminated liquid nitrile rubber, a diluent and a polyurethane prepolymer to obtain a mixed solution; (2) mixing a hydrophobic material, a hydrogen-resistant material and the mixed solution to obtain a dispersion solution; and (3) mixing the dispersion liquid with a curing agent. The composite coating disclosed by the invention can be used for retarding the occurrence of a metal hydrogen embrittlement phenomenon by inhibiting remarkable hydrogen permeation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of composite materials, and in particular to a composite coating and a preparation method and application thereof. Background Art

[0002] Hydrogen energy has the advantages of wide sources, high energy conversion rate, no pollution, zero emissions, and renewable. It is an ideal carrier to promote the large-scale development of renewable energy and occupies an important position in the future energy landscape. However, in the presence of hydrogen, hydrogen embrittlement of metal materials occurs due to hydrogen absorption and hydrogen permeation, which seriously degrades the mechanical properties of metal materials, seriously affecting the service life and reliability of metal parts of hydrogen-containing equipment. In severe cases, hydrogen leakage may cause safety accidents. Therefore, improving the hydrogen barrier properties of polymer-based coatings that can be applied to metal surfaces and have hydrogen barrier properties is a current research difficulty in this field.

[0003] The epoxy resin hydrogen barrier coating currently studied mainly adds the interaction between molybdate corrosion inhibitor and silane coupling agent to form a hydrogen permeation barrier film to play a hydrogen permeation barrier effect (CN 107916045A). As a traditional thermosetting polymer, epoxy resin (EP) has a high cross-linking density that gives it high tensile strength, Young's modulus, low creep, excellent dimensional stability and thermal stability. The EP three-dimensional network structure formed by high cross-linking density also causes the coating to have greater brittleness, fragility, low fracture toughness, poor crack resistance and other shortcomings, thereby further reducing the hydrogen barrier performance of epoxy resin coatings, and the hydrogen barrier performance of epoxy resin coatings is poor, so it cannot effectively suppress the occurrence of hydrogen embrittlement. In addition, studies have shown that the presence of water vapor promotes the hydrogen embrittlement behavior of metal materials.

[0004] Patent application CN 107916045 A discloses a hydrogen-blocking material and a preparation method thereof, which mainly improves the ability to resist pitting corrosion by adding molybdate and silane coupling agent and their interaction to self-heal, and deposits reduction products on the metal surface to form a film that blocks hydrogen diffusion, thereby enhancing the ability to block hydrogen penetration, so that the prepared material has a good effect of blocking hydrogen penetration. However, this solution does not improve the hydrogen barrier ability from the structural essence of the base material.

[0005] Patent application CN 115181276 A discloses a modified epoxy resin and a preparation method thereof, an epoxy resin coating and a preparation method thereof, and an application thereof. This solution obtains a modified epoxy resin by grafting a fluorine-containing polymer to a chain segment of an epoxy resin, thereby improving its hydrophobicity and thermal stability, and enhancing its corrosion resistance. This solves the technical problems of poor hydrophobicity, poor acid resistance, and unsatisfactory modification effect of epoxy resins in the prior art, and achieves the technical effect of improving the hydrophobicity and thermal stability of epoxy resins and making them more resistant to corrosion. However, this solution does not involve the hydrogen barrier properties of the material. Summary of the invention

[0006] The purpose of the present invention is to overcome the technical problem that the existing hydrogen barrier coating has poor hydrogen barrier performance, and to provide a composite coating and its preparation method and application. The composite coating has good hydrogen barrier performance and can be used for spraying and coating the surface of metal materials in all hydrogen environments.

[0007] In order to achieve the above-mentioned object, the present invention provides a composite coating on one hand, wherein the raw materials for preparing the composite coating contain epoxy resin, carboxyl-terminated liquid nitrile rubber, polyurethane prepolymer, hydrophobic material and hydrogen barrier material.

[0008] Preferably, the hydrogen permeation current density of the composite coating is 0.1-0.28 μA / cm 2 .

[0009] Preferably, the hydrophobic material is SiO2 and / or graphene.

[0010] Preferably, the average particle size of the SiO2 is 50-800nm.

[0011] Preferably, the number of graphene layers is 5-70.

[0012] Preferably, the hydrogen barrier material is one or more of Al2O3, SiC and Ti3C2 nanosheets.

[0013] Preferably, the average particle size of the Al2O3 is 20nm-1μm.

[0014] Preferably, the average particle size of the SiC is 50-800 nm.

[0015] Preferably, the number of layers of the Ti3C2 nanosheets is 8-40.

[0016] Preferably, the epoxy resin is selected from E51 and / or E44.

[0017] Preferably, the number average molecular weight of the polyurethane prepolymer is 10,000-500,000.

[0018] Preferably, the polyurethane prepolymer is polyether polyurethane and / or polyester polyurethane.

[0019] Preferably, the raw materials for preparing the composite coating also contain additives.

[0020] Preferably, the auxiliary agent contains a curing agent and a diluent.

[0021] Preferably, the diluent is selected from one or more of xylene, n-butanol and dimethylformamide.

[0022] Preferably, the curing agent is one or more of polyamide, triethylenetetramine and 3,3'-dichloro-4,4'-diaminodiphenylmethane.

[0023] A second aspect of the present invention provides a method for preparing a composite coating, the method comprising the following steps:

[0024] (1) mixing epoxy resin, carboxyl-terminated liquid nitrile rubber, a diluent and a polyurethane prepolymer to obtain a mixed solution;

[0025] (2) mixing a hydrophobic material, a hydrogen barrier material and the mixed liquid to obtain a dispersion;

[0026] (3) Mixing the dispersion and the curing agent.

[0027] Preferably, the specific steps of step (1) include:

[0028] (a) an epoxy resin and a carboxyl-terminated liquid nitrile rubber are subjected to vacuum stirring and then mixed with a diluent to obtain a solution A;

[0029] (b) vacuum stirring the polyurethane prepolymer and the solution A to obtain a mixed solution.

[0030] Preferably, based on the total amount of epoxy resin, carboxyl-terminated liquid nitrile rubber and polyurethane prepolymer as 100 weight %, the amount of polyurethane prepolymer is 5-80 weight %, the amount of carboxyl-terminated liquid nitrile rubber is 10-70 weight %, and the amount of epoxy resin is 10-85 weight %.

[0031] Preferably, the weight ratio of the amount of the diluent to the total amount of the epoxy resin, the carboxyl-terminated liquid nitrile rubber and the polyurethane prepolymer is 10-80:100.

[0032] Preferably, in step (a), the vacuum stirring conditions include: a temperature of 30-120°C, a vacuum degree of -0.5×10 5 Pa~-1×10 5 Pa, speed 400-600rmp, time 20-40min;

[0033] Preferably, in step (b), the vacuum stirring conditions include: a temperature of 30-120°C, a vacuum degree of -0.5×10 5 Pa~-1×10 5 Pa, speed is 400-600rmp, time is 20-40min.

[0034] Preferably, the specific steps of step (2) include:

[0035] S1, vacuum stirring the hydrophobic material and the mixed solution;

[0036] S2. The material obtained in step S1 and the hydrogen barrier material are vacuum stirred to obtain a dispersion.

[0037] Preferably, the weight ratio of the amount of the hydrophobic material to the amount of the mixed solution is 1-10:100;

[0038] Preferably, the weight ratio of the amount of the hydrogen barrier material to the amount of the mixed liquid is 1-15:100.

[0039] Preferably, in step S1, the vacuum stirring conditions include: a temperature of 30-120°C, a vacuum degree of -0.5×10 5 Pa~-1×10 5 Pa, speed 100-1000rmp, time 20-40min;

[0040] Preferably, in step S2, the vacuum stirring conditions include: a temperature of 30-120°C, a vacuum degree of -0.5×10 5 Pa~-1×10 5 Pa, speed is 3000-5000rmp, time is 20-40min.

[0041] Preferably, in step (3), the weight ratio of the amount of the curing agent to the amount of the dispersion is 5-50:100.

[0042] Preferably, in step (3), the mixing operation is vacuum stirring.

[0043] Preferably, the vacuum stirring conditions include: temperature of 30-120°C, vacuum degree of -0.5×10 5 Pa~-1×10 5 Pa, speed is 3000-5000rmp, time is 20-40min.

[0044] A third aspect of the present invention provides an application of the above-mentioned composite coating in hydrogen embrittlement protection of metal materials.

[0045] The present invention uses epoxy resin, carboxyl-terminated liquid nitrile rubber, polyurethane prepolymer, hydrophobic material and hydrogen barrier material as raw materials to prepare a composite coating with good hydrogen barrier performance, and further adjusts the hydrogen barrier performance of the composite coating by adjusting the ratio among the epoxy resin, the polyurethane prepolymer and the carboxyl-terminated liquid nitrile rubber and the molecular weight of the polyurethane prepolymer, the ratio of the hydrophobic material and the hydrogen barrier material and their size effect, the vacuum stirring temperature and the stirring speed. DETAILED DESCRIPTION

[0046] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0047] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0048] On one hand, the present invention provides a composite coating. The raw materials for preparing the composite coating contain epoxy resin, carboxyl-terminated liquid nitrile rubber, polyurethane prepolymer, hydrophobic material and hydrogen barrier material.

[0049] In the present invention, due to the presence of the hydrophobic material, the obtained composite coating will have hydrophobicity, which can reduce the hydrogen embrittlement phenomenon formed on the metal surface due to the coupling effect of hydrogen and water vapor, further reduce the hydrogen absorption and hydrogen permeation phenomenon, and help improve the hydrogen barrier performance.

[0050] In a preferred embodiment, the hydrogen permeation current density of the composite coating of the present invention is 0.1-0.28 μA / cm 2 .

[0051] Further preferably, the hydrophobic material is SiO2 and / or graphene.

[0052] When the average particle size of SiO2 is different, its dispersion degree in the composite coating is different, which will affect the mechanical properties and hydrogen barrier properties of the composite coating. Therefore, in the preferred case, in order to improve the mechanical properties and hydrogen barrier properties of the obtained composite coating, the average particle size of SiO2 is 50-800nm.

[0053] In the present invention, since the number of graphene layers is different, the path through which the gas passes will be different. When the number of graphene layers is large, the effect of extending the hydrogen transmission path can be achieved, thereby playing a significant hydrogen barrier effect. Therefore, in order to improve the hydrogen barrier performance, in a preferred embodiment, the number of graphene layers is 5-70 layers.

[0054] Further preferably, the hydrogen barrier material is one or more of Al2O3, SiC and Ti3C2 nanosheets.

[0055] In a preferred embodiment, the average particle size of the Al2O3 is 20 nm-1 μm.

[0056] Preferably, the average particle size of the SiC is 50-800 nm.

[0057] In the present invention, the number of layers of Ti3C2 nanosheets may be different. When the number of layers of Ti3C2 nanosheets is different, the hydrogen barrier performance is different. The more layers there are, the longer the distance that hydrogen molecules need to pass through, and the better the hydrogen barrier performance. Therefore, in a preferred case, the number of layers of the Ti3C2 nanosheets is 8-40 layers.

[0058] Also in the present invention, when the average particle sizes of Al2O3 and SiC are different, their dispersion degrees in the composite coating are different, which will affect the mechanical properties and hydrogen barrier properties of the composite coating. Therefore, in order to improve the performance of the composite coating, in a preferred case, the average particle sizes of Al2O3 and SiC are controlled within the above range.

[0059] Preferably, the epoxy resin is selected from E51 and / or E44.

[0060] More preferably, the number average molecular weight of the polyurethane prepolymer is 10,000-500,000, specifically 10,000, 100,000, 200,000, 300,000, 400,000 or 500,000.

[0061] Preferably, the polyurethane prepolymer is polyether polyurethane and / or polyester polyurethane.

[0062] In the present invention, in order to further obtain a composite coating with better performance, the raw materials for preparing the composite coating also contain an auxiliary agent.

[0063] Preferably, the auxiliary agent contains a curing agent and a diluent.

[0064] Preferably, the diluent is selected from one or more of xylene, n-butanol and dimethylformamide.

[0065] Preferably, the curing agent is one or more of polyamide, triethylenetetramine and 3,3'-dichloro-4,4'-diaminodiphenylmethane.

[0066] In the present invention, the composite coating prepared by using the above raw materials has good hydrogen barrier performance, and its hydrogen permeation current density is 0.1-0.28μA / cm 2 .

[0067] In the present invention, the test method of the hydrogen permeation current density is to use a Devnathan-Stachurski double electrolytic cell to conduct a hydrogen diffusion experiment to obtain the hydrogen permeation current, and further obtain the hydrogen permeation current density.

[0068] A second aspect of the present invention provides a method for preparing a composite coating, the method comprising the following steps:

[0069] (1) mixing epoxy resin, carboxyl-terminated liquid nitrile rubber, a diluent and a polyurethane prepolymer to obtain a mixed solution;

[0070] (2) mixing a hydrophobic material, a hydrogen barrier material and the mixed liquid to obtain a dispersion;

[0071] (3) Mixing the dispersion and the curing agent.

[0072] Preferably, the specific steps of step (1) include:

[0073] (a) an epoxy resin and a carboxyl-terminated liquid nitrile rubber are subjected to vacuum stirring and then mixed with a diluent to obtain a solution A;

[0074] (b) vacuum stirring the polyurethane prepolymer and the solution A to obtain a mixed solution.

[0075] In the method for preparing a composite coating described in the present invention, adsorbed water may exist in raw materials such as epoxy resin, carboxyl-terminated liquid nitrile rubber and polyurethane prepolymer. During the preparation process, the adsorbed water will participate in the chemical reaction, thereby affecting the performance of the composite coating. Therefore, in order to obtain a composite coating with better performance, in a preferred case, all raw materials such as epoxy resin, carboxyl-terminated liquid nitrile rubber and polyurethane prepolymer need to be placed in a vacuum oven for drying in advance, and the drying temperature is controlled to be 50-100°C, the drying time is 30-150min, and then mixed after drying, in order to remove the adsorbed water in all raw materials.

[0076] Preferably, in order to further improve the performance of the composite coating, it is necessary to reasonably control the proportion and dosage of the raw materials, wherein, based on the total dosage of the epoxy resin, the carboxyl-terminated liquid nitrile rubber and the polyurethane prepolymer as 100 weight %, the dosage of the polyurethane prepolymer is 5-80 weight %, the dosage of the carboxyl-terminated liquid nitrile rubber is 10-70 weight %, and the dosage of the epoxy resin is 10-85 weight %.

[0077] Preferably, the weight ratio of the amount of the diluent to the total amount of the epoxy resin, the carboxyl-terminated liquid nitrile rubber and the polyurethane prepolymer is 10-80:100. Specifically, the weight ratio of the amount of the diluent to the total amount of the epoxy resin, the carboxyl-terminated liquid nitrile rubber and the polyurethane prepolymer can be 10:100, 20:100, 30:100, 40:100, 50:100, 60:100, 70:100 or 80:100.

[0078] In the present invention, the raw materials are mixed in a vacuum stirring manner, which can make the raw materials mixed more fully on the one hand, and can also avoid the generation of bubbles in the mixing process to reduce the performance of the composite coating on the other hand.

[0079] Preferably, in step (a), the vacuum stirring conditions include: a temperature of 30-120°C, a vacuum degree of -0.5×10 5 Pa~-1×10 5 Pa, speed is 400-600rmp, time is 20-40min.

[0080] In a specific embodiment, in step (a), the temperature of the vacuum stirring may be 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C, and the vacuum degree of the vacuum stirring may be -0.5×10 5 Pa, -0.6×10 5 Pa, -0.7×10 5 Pa, -0.8×10 5 Pa, -0.9×10 5 Pa or -1×10 5 Pa, the rotation speed of the vacuum stirring can be 400rmp, 450rmp, 500rmp, 550rmp or 600rmp, and the time of the vacuum stirring can be 20min, 25min, 30min, 35min or 40min.

[0081] Preferably, in step (b), the vacuum stirring conditions include: a temperature of 30-120°C, a vacuum degree of -0.5×10 5 Pa~-1×10 5 Pa, speed is 400-600rmp, time is 20-40min.

[0082] In a specific embodiment, in step (b), the temperature of the vacuum stirring may be 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C, and the vacuum degree of the vacuum stirring may be -0.5×10 5 Pa, -0.6×10 5Pa, -0.7×10 5 Pa, -0.8×10 5 Pa, -0.9×10 5 Pa or -1×10 5 Pa, the rotation speed of the vacuum stirring can be 400rmp, 450rmp, 500rmp, 550rmp or 600rmp, and the time of the vacuum stirring can be 20min, 25min, 30min, 35min or 40min.

[0083] Preferably, the specific steps of step (2) include:

[0084] S1, vacuum stirring the hydrophobic material and the mixed solution;

[0085] S2. The material obtained in step S1 and the hydrogen barrier material are vacuum stirred to obtain a dispersion.

[0086] Further preferably, in order to improve the dispersibility of the hydrophobic material and the hydrogen barrier material so as to further improve the performance of the composite coating, the hydrophobic material and the hydrogen barrier material need to be modified with a silane coupling agent before mixing.

[0087] Therefore, in a preferred embodiment, in step S1, the hydrophobic material is stirred with methanol, water and silane coupling agent A for 0.5-1.5 hours, then filtered, the obtained solid is dried, and then vacuum stirred with the mixed solution.

[0088] Wherein, in step S1, the ratio of the amount of hydrophobic material, methanol, water and silane coupling agent A is 1g:20-60mL:5-12mL:1-5mL.

[0089] In the present invention, the modification treatment of the hydrophobic material with a silane coupling agent is a conventional treatment method in the art, and the silane coupling agent A used is also a silane coupling agent conventionally used in the art. In a specific embodiment, the silane coupling agent A is selected from one or more of KH560, KH550 and KH570.

[0090] Also in a preferred embodiment, in step S2, the hydrogen barrier material is stirred with methanol, water and silane coupling agent B for 0.5-1.5 hours, then filtered, the obtained solid is dried, and then vacuum stirred with the material obtained in step S1 to obtain a dispersion.

[0091] Wherein, in step S2, the ratio of the amount of hydrogen barrier material, methanol, water and silane coupling agent B is 1g:10-50mL:3-11mL:2-6mL.

[0092] In the present invention, the modification treatment of the hydrogen barrier material with a silane coupling agent is a conventional treatment method in the art, and the silane coupling agent B used is also a silane coupling agent conventionally used in the art. In a specific embodiment, the silane coupling agent B is selected from one or more of KH560, KH550 and KH570.

[0093] In the preferred case of step S1, the weight ratio of the hydrophobic material to the mixed solution is 1-10:100, specifically 1:100, 2:100, 3:100, 4:100, 5:100, 6:100, 7:100, 8:100, 9:100 or 10:100.

[0094] In the preferred case of step S2, the weight ratio of the amount of the hydrogen barrier material to the amount of the mixed solution is 1-15:100, more preferably 1-10:100, specifically 1:100, 3:100, 5:100, 7:100, 9:100 or 10:100.

[0095] In a preferred embodiment, in step S1, the vacuum stirring conditions include: a temperature of 30-120°C, a vacuum degree of -0.5×10 5 Pa~-1×10 5 Pa, speed is 100-1000rmp, time is 20-40min.

[0096] In a specific embodiment, in step S1, the temperature of the vacuum stirring may be 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C, and the vacuum degree of the vacuum stirring may be -0.5×10 5 Pa, -0.6×10 5 Pa, -0.7×10 5 Pa, -0.8×10 5 Pa, -0.9×10 5 Pa or -1×10 5 Pa, the rotation speed of the vacuum stirring can be 100rmp, 200rmp, 300rmp, 400rmp, 500rmp, 600rmp, 700rmp, 800rmp, 900rmp or 1000rmp, and the time of the vacuum stirring can be 20min, 25min, 30min, 35min or 40min.

[0097] In a preferred embodiment, in step S2, the vacuum stirring conditions include: a temperature of 30-120°C, a vacuum degree of -0.5×10 5 Pa~-1×10 5Pa, speed is 3000-5000rmp, time is 20-40min.

[0098] In a specific embodiment, in step S2, the temperature of the vacuum stirring may be 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C, and the vacuum degree of the vacuum stirring may be -0.5×10 5 Pa, -0.6×10 5 Pa, -0.7×10 5 Pa, -0.8×10 5 Pa, -0.9×10 5 Pa or -1×10 5 Pa, the rotation speed of the vacuum stirring can be 3000rmp, 3500rmp, 4000rmp, 4500rmp or 5000rmp, and the time of the vacuum stirring can be 20min, 25min, 30min, 35min or 40min.

[0099] Preferably, in step (3), the weight ratio of the amount of the curing agent to the amount of the dispersion is 5-50:100, more preferably 20-50:100, specifically 20:100, 30:100, 40:100 or 50:100.

[0100] Preferably, in step (3), the mixing operation is vacuum stirring.

[0101] Preferably, in step (3), the vacuum stirring conditions include: a temperature of 30-120°C, a vacuum degree of -0.5×10 5 Pa~-1×10 5 Pa, speed is 3000-5000rmp, time is 20-40min.

[0102] In a specific embodiment, in step (3), the temperature of the vacuum stirring may be 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C, and the vacuum degree of the vacuum stirring may be -0.5×10 5 Pa, -0.6×10 5 Pa, -0.7×10 5 Pa, -0.8×10 5 Pa, -0.9×10 5 Pa or -1×10 5Pa, the rotation speed of the vacuum stirring can be 3000rmp, 3500rmp, 4000rmp, 4500rmp or 5000rmp, and the time of the vacuum stirring can be 20min, 25min, 30min, 35min or 40min.

[0103] In the method described in the present invention, the operation of adding the raw materials step by step to react is conducive to forming a polymer material with a high degree of cross-linking, thereby being more conducive to improving the hydrogen barrier performance.

[0104] A third aspect of the present invention provides an application of the above-mentioned composite coating in hydrogen embrittlement protection of metal materials.

[0105] The present invention controls the ratio of epoxy resin, carboxyl-terminated liquid nitrile rubber and polyurethane prepolymer through the design of material structures of different dimensions, so that a chemical cross-linking grafting reaction occurs between the molecular structures of the ternary matrix; the ternary matrix further forms hydrogen bonds with hydrophobic particles and hydrogen-blocking micro-nano fillers, and finally further reacts chemically with a curing agent to greatly increase the cross-linking density of the coating; so that a ternary interpenetrating network structure coating is formed, and the coating has significant hydrogen barrier properties, effectively reduces hydrogen permeability, and can effectively inhibit the occurrence of metal hydrogen embrittlement; in addition, the introduction of hydrophobic materials can significantly reduce the enrichment of water molecules on the surface of the hydrogen transmission pipeline, thereby further inhibiting the hydrogen embrittlement caused by the coupling of hydrogen and water vapor.

[0106] The composite coating of the present invention can slow down the occurrence of metal hydrogen embrittlement by inhibiting significant hydrogen permeation, thereby improving the service life and reliability of metal parts of hydrogen-containing equipment, and can be applied to the spraying and coating of metal material surfaces in all hydrogen-containing environments, and has broad application prospects in the above-mentioned fields and related fields.

[0107] The present invention will be described in detail below through examples, but the protection scope of the present invention is not limited thereto.

[0108] In the following examples, epoxy resin was purchased from Jiangsu Nantong Xingchen Synthetic Materials Co., Ltd., carboxyl-terminated liquid nitrile rubber was purchased from Shenzhen Masni Elastomer Co., Ltd., and polyurethane prepolymer was purchased from Chemtura.

[0109] Example 1

[0110] (1) epoxy resin (E51), carboxyl-terminated liquid nitrile rubber, diluent (xylene), polyurethane prepolymer (polyether polyurethane) with a number average molecular weight of 10,000, hydrophobic material (SiO2 with an average particle size of 50 nm), hydrogen barrier material (Al2O3 with an average particle size of 20 nm), and curing agent (polyamide) were placed in a vacuum oven and dried at 70°C for 80 min;

[0111] (2) adding the dried hydrophobic material to methanol and silane coupling agent A (KH550), wherein the ratio of the dried hydrophobic material, methanol, water and silane coupling agent A is 1 g: 20 mL: 5 mL: 1.25 mL, stirring for 1 hour, and then filtering, and drying the obtained solid to obtain a silane coupling agent modified hydrophobic material;

[0112] (3) adding the dried hydrogen barrier material to methanol and silane coupling agent B (KH560), wherein the ratio of the dried hydrogen barrier material, methanol, water and silane coupling agent B is 1 g: 40 mL: 10 mL: 2.5 mL, stirring for 1 h, then filtering, and drying the obtained solid to obtain a silane coupling agent modified hydrogen barrier material;

[0113] (4) Add the dried epoxy resin to the dried carboxyl-terminated liquid nitrile rubber and stir under vacuum (temperature 50°C, vacuum degree -1.0×10 5 Pa, speed of 500 rpm, time of 20 min), then add the dried diluent, mix well to obtain solution A; add solution A to the dried polyurethane prepolymer, and perform vacuum stirring (temperature of 30°C, vacuum degree of -1.0×10 5 Pa, a speed of 500rmp, and a time of 30min) to obtain a mixed solution; wherein the total amount of the dried epoxy resin, the dried carboxyl-terminated liquid nitrile rubber and the dried polyurethane prepolymer is 100% by weight, the content of the dried polyurethane prepolymer is 5% by weight, the content of the dried carboxyl-terminated liquid nitrile rubber is 10% by weight, and the content of the dried epoxy resin is 85% by weight; wherein the weight ratio of the amount of the dried diluent to the total amount of the dried epoxy resin, the dried carboxyl-terminated liquid nitrile rubber and the dried polyurethane prepolymer is 10:100;

[0114] (5) Adding a silane coupling agent-modified hydrophobic material to the mixed solution, the weight ratio of the silane coupling agent-modified hydrophobic material to the mixed solution is 10:100, and then vacuum stirring is performed (temperature is 30°C, vacuum degree is -1.0×10 5 Pa, speed 100rmp, time 30min);

[0115] (6) Adding a silane coupling agent modified hydrogen barrier material to the material obtained in step (5), the weight ratio of the silane coupling agent modified hydrogen barrier material to the mixed solution is 10:100, and then vacuum stirring (temperature is 30°C, vacuum degree is -1.0×10 5 Pa, speed of 3000rmp, time of 30min), and obtain a dispersion after uniform dispersion;

[0116] (7) Add the dried curing agent to the dispersion, the weight ratio of the dried curing agent to the dispersion is 25:100, and then vacuum stir (temperature is 30°C, vacuum degree is -1.0×10 5 Pa, rotation speed of 3000rmp, time of 30min), and then the composite coating A1 was obtained.

[0117] Example 2

[0118] (1) placing epoxy resin (E51), carboxyl-terminated liquid nitrile rubber, diluent (xylene), polyurethane prepolymer (polyether polyurethane) with a number average molecular weight of 500,000, hydrophobic material (graphene with 5 to 30 layers), hydrogen barrier material (SiC with an average particle size of 50 nm), and curing agent (triethylenetetramine) in a vacuum oven, and drying at 80° C. for 120 min;

[0119] (2) adding the dried hydrophobic material to methanol and silane coupling agent A (KH550), wherein the ratio of the dried hydrophobic material, methanol, water and silane coupling agent A is 1 g: 30 mL: 10 mL: 2 mL, stirring for 1 h, and then filtering, and drying the obtained solid to obtain a silane coupling agent modified hydrophobic material;

[0120] (3) adding the dried hydrogen barrier material to methanol and silane coupling agent B (KH550), wherein the ratio of the dried hydrogen barrier material, methanol, water and silane coupling agent B is 1 g: 40 mL: 8 mL: 5 mL, stirring for 1 h, then filtering, and drying the obtained solid to obtain a silane coupling agent modified hydrogen barrier material;

[0121] (4) Add the dried epoxy resin to the dried carboxyl-terminated liquid nitrile rubber and stir under vacuum (temperature 40°C, vacuum degree -1.0×10 5 Pa, speed 500rmp, time 30min), then add the dried diluent, mix evenly to obtain solution A; add solution A to the dried polyurethane prepolymer, and perform vacuum stirring (temperature 30°C, vacuum degree -1.0×10 5 Pa, a speed of 500rmp, and a time of 30min) to obtain a mixed solution; wherein the total amount of the dried epoxy resin, the dried carboxyl-terminated liquid nitrile rubber and the dried polyurethane prepolymer is 100% by weight, the content of the dried polyurethane prepolymer is 80% by weight, the content of the dried carboxyl-terminated liquid nitrile rubber is 10% by weight, and the content of the dried epoxy resin is 10% by weight; wherein the weight ratio of the amount of the dried diluent to the total amount of the dried epoxy resin, the dried carboxyl-terminated liquid nitrile rubber and the dried polyurethane prepolymer is 80:100;

[0122] (5) Adding a silane coupling agent-modified hydrophobic material to the mixed solution, the weight ratio of the silane coupling agent-modified hydrophobic material to the mixed solution is 10:100, and then vacuum stirring is performed (temperature is 30°C, vacuum degree is -1.0×10 5 Pa, speed 1000rmp, time 30min);

[0123] (6) Adding a silane coupling agent modified hydrogen barrier material to the material obtained in step (5), wherein the weight ratio of the silane coupling agent modified hydrogen barrier material to the mixed solution is 1:100, and then vacuum stirring is performed (temperature is 30°C, vacuum degree is -1.0×10 5 Pa, speed of 5000rmp, time of 30min), and obtain a dispersion after uniform dispersion;

[0124] (7) Add the dried curing agent to the dispersion, the weight ratio of the dried curing agent to the dispersion is 50:100, and then vacuum stir (temperature is 30°C, vacuum degree is -1.0×10 5 Pa, rotation speed of 3000rmp, time of 30min), and then the composite coating A2 was obtained.

[0125] Example 3

[0126] (1) placing epoxy resin (E51), carboxyl-terminated liquid nitrile rubber, diluent (xylene), polyurethane prepolymer (polyester polyurethane) with a number average molecular weight of 200,000, hydrophobic material (graphene with 30 to 50 layers and SiO2 with an average particle size of 800 nm), hydrogen barrier material (SiC with an average particle size of 800 nm and Al2O3 with an average particle size of 1 μm) and curing agent (triethylenetetramine and polyamide) in a vacuum oven and drying at 50° C. for 150 min;

[0127] (2) adding the dried hydrophobic material to methanol and silane coupling agent A (KH560), wherein the ratio of the dried hydrophobic material, methanol, water and silane coupling agent A is 1 g: 60 mL: 10 mL: 3 mL, stirring for 1 h, then filtering, and drying the obtained solid to obtain a silane coupling agent modified hydrophobic material;

[0128] (3) adding the dried hydrogen barrier material to methanol and silane coupling agent B (KH560), wherein the ratio of the dried hydrogen barrier material, methanol, water and silane coupling agent B is 1 g: 20 mL: 11 mL: 6 mL, stirring for 1 h, then filtering, and drying the obtained solid to obtain a silane coupling agent modified hydrogen barrier material;

[0129] (4) Add the dried epoxy resin to the dried carboxyl-terminated liquid nitrile rubber and stir under vacuum (temperature 60°C, vacuum degree -1.0×10 5 Pa, speed 600rmp, time 30min), then add the dried diluent, mix evenly to obtain solution A; add solution A to the dried polyurethane prepolymer, and perform vacuum stirring (temperature 30°C, vacuum degree -1.0×10 5 Pa, speed of 500rmp, time of 30min), to obtain a mixed solution; wherein the total amount of the dried epoxy resin, the dried carboxyl-terminated liquid nitrile rubber and the dried polyurethane prepolymer is 100% by weight, the content of the dried polyurethane prepolymer is 65% by weight, the content of the dried carboxyl-terminated liquid nitrile rubber is 10% by weight, and the content of the dried epoxy resin is 25% by weight; wherein the weight ratio of the amount of the dried diluent to the total amount of the dried epoxy resin, the dried carboxyl-terminated liquid nitrile rubber and the dried polyurethane prepolymer is 30:100;

[0130] (5) Adding a silane coupling agent modified hydrophobic material to the mixed solution, the weight ratio of the silane coupling agent modified hydrophobic material to the mixed solution is 8.5:100 (the weight ratio of the silane coupling agent modified graphene to the mixed solution is 0.5:100, and the weight ratio of the silane coupling agent modified SiO2 to the mixed solution is 8:100), and then vacuum stirring is performed (the temperature is 30°C, the vacuum degree is -1.0×10 5 Pa, speed 300rmp, time 30min);

[0131] (6) Adding a silane coupling agent modified hydrogen barrier material to the material obtained in step (5), the weight ratio of the amount of the silane coupling agent modified hydrogen barrier material to the amount of the mixed solution is 10:100 (the weight ratio of the amount of the silane coupling agent modified SiC to the amount of the mixed solution is 2:100, and the weight ratio of the amount of the silane coupling agent modified Al2O3 to the amount of the mixed solution is 8:100), and then vacuum stirring is performed (the temperature is 30°C, the vacuum degree is -1.0×10 5 Pa, speed of 5000rmp, time of 30min), and obtain a dispersion after uniform dispersion;

[0132] (7) Add the dried curing agent to the dispersion, the weight ratio of the dried curing agent to the dispersion is 35:100, and then vacuum stir (temperature is 30°C, vacuum degree is -1.0×10 5 Pa, rotation speed of 3000rmp, time of 30min) to obtain a composite coating A3.

[0133] Example 4

[0134] (1) epoxy resin (E51), carboxyl-terminated liquid nitrile rubber, diluent (xylene), polyurethane prepolymer (polyester polyurethane) with a number average molecular weight of 300,000, hydrophobic material (Ti3C2 nanosheets with 15-40 layers and SiO2 with an average particle size of 100 nm), hydrogen barrier material (SiC with an average particle size of 100 nm and Al2O3 with an average particle size of 500 nm) and curing agent (polyamide) were placed in a vacuum oven and dried at 100°C for 40 min;

[0135] (2) adding the dried hydrophobic material to methanol and silane coupling agent A (KH570), wherein the ratio of the dried hydrophobic material, methanol, water and silane coupling agent A is 1 g:45 mL:12 mL:1 mL, stirring for 1 h, then filtering, and drying the obtained solid to obtain a silane coupling agent modified hydrophobic material;

[0136] (3) adding the dried hydrogen barrier material to methanol and silane coupling agent B (KH570), wherein the ratio of the dried hydrogen barrier material, methanol, water and silane coupling agent B is 1 g: 10 mL: 10 mL: 2 mL, stirring for 1 h, then filtering, and drying the obtained solid to obtain a silane coupling agent modified hydrogen barrier material;

[0137] (4) Add the dried epoxy resin to the dried carboxyl-terminated liquid nitrile rubber and stir under vacuum (temperature 50°C, vacuum degree -1.0×10 5 Pa, speed 500rmp, time 20min), then add the dried diluent, mix evenly to obtain solution A; add solution A to the dried polyurethane prepolymer, and stir under vacuum (temperature 30°C, vacuum degree -1.0×10 5 Pa, speed of 500rmp, time of 30min), to obtain a mixed solution; wherein the total amount of the dried epoxy resin, the dried carboxyl-terminated liquid nitrile rubber and the dried polyurethane prepolymer is 100% by weight, the content of the dried polyurethane prepolymer is 15% by weight, the content of the dried carboxyl-terminated liquid nitrile rubber is 70% by weight, and the content of the dried epoxy resin is 15% by weight; wherein the weight ratio of the amount of the dried diluent to the total amount of the dried epoxy resin, the dried carboxyl-terminated liquid nitrile rubber and the dried polyurethane prepolymer is 60:100;

[0138] (5) Adding a silane coupling agent modified hydrophobic material to the mixed solution, the weight ratio of the silane coupling agent modified hydrophobic material to the mixed solution is 10:100 (the weight ratio of the silane coupling agent modified Ti3C2 nanosheets to the mixed solution is 8:100, and the weight ratio of the silane coupling agent modified SiO2 to the mixed solution is 2:100), and then vacuum stirring is performed (the temperature is 30°C, the vacuum degree is -1.0×10 5 Pa, speed 500rmp, time 30min);

[0139] (6) Adding a silane coupling agent modified hydrogen barrier material to the material obtained in step (5), the weight ratio of the amount of the silane coupling agent modified hydrogen barrier material to the amount of the mixed solution is 10:100 (the weight ratio of the amount of the silane coupling agent modified SiC to the amount of the mixed solution is 7:100, and the weight ratio of the amount of the silane coupling agent modified Al2O3 to the amount of the mixed solution is 3:100), and then vacuum stirring is performed (the temperature is 30°C, the vacuum degree is -1.0×10 5 Pa, speed of 4000rmp, time of 30min), and obtain a dispersion after uniform dispersion;

[0140] (7) Add the dried curing agent to the dispersion, the weight ratio of the dried curing agent to the dispersion is 28:100, and then vacuum stir (temperature is 30°C, vacuum degree is -1.0×10 5 Pa, rotation speed of 3000rmp, time of 30min) to obtain a composite coating A4.

[0141] Example 5

[0142] (1) placing epoxy resin (E51), carboxyl-terminated liquid nitrile rubber, diluent (xylene), polyurethane prepolymer (polyester polyurethane) with a number average molecular weight of 100,000, hydrophobic material (SiO2 with an average particle size of 150 nm), hydrogen barrier material (SiC with an average particle size of 350 nm), and curing agent (polyamide) in a vacuum oven and drying at 90°C for 140 min;

[0143] (2) adding the dried hydrophobic material to methanol and silane coupling agent A (KH560), wherein the ratio of the dried hydrophobic material, methanol, water and silane coupling agent A is 1 g: 20 mL: 12 mL: 4 mL, stirring for 1 h, stirring, and then filtering, and drying the obtained solid to obtain a silane coupling agent modified hydrophobic material;

[0144] (3) adding the dried hydrogen barrier material to methanol and silane coupling agent B (KH570), wherein the ratio of the dried hydrogen barrier material, methanol, water and silane coupling agent B is 1 g: 35 mL: 4 mL: 6 mL, stirring for 1 h, then filtering, and drying the obtained solid to obtain a silane coupling agent modified hydrogen barrier material;

[0145] (4) Add the dried epoxy resin to the dried carboxyl-terminated liquid nitrile rubber and stir under vacuum (temperature 50°C, vacuum degree -0.7×10 5 Pa, speed of 500 rpm, time of 20 min), then add the dried diluent, mix well to obtain solution A; add solution A to the dried polyurethane prepolymer, and perform vacuum stirring (temperature of 30°C, vacuum degree of -1.0×10 5 Pa, a speed of 500rmp, and a time of 30min) to obtain a mixed solution; wherein the total amount of the dried epoxy resin, the dried carboxyl-terminated liquid nitrile rubber and the dried polyurethane prepolymer is 100% by weight, the content of the dried polyurethane prepolymer is 20% by weight, the content of the dried carboxyl-terminated liquid nitrile rubber is 60% by weight, and the content of the dried epoxy resin is 20% by weight; wherein the weight ratio of the amount of the dried diluent to the total amount of the dried epoxy resin, the dried carboxyl-terminated liquid nitrile rubber and the dried polyurethane prepolymer is 30:100;

[0146] (5) Adding a silane coupling agent-modified hydrophobic material to the mixed solution, the weight ratio of the silane coupling agent-modified hydrophobic material to the mixed solution is 10:100, and then vacuum stirring is performed (temperature is 30°C, vacuum degree is -1.0×10 5 Pa, speed 300rmp, time 30min);

[0147] (6) Adding a silane coupling agent modified hydrogen barrier material to the material obtained in step (5), the weight ratio of the silane coupling agent modified hydrogen barrier material to the mixed solution is 10:100, and then vacuum stirring (temperature is 30°C, vacuum degree is -1.0×10 5 Pa, speed of 3000rmp, time of 30min), and obtain a dispersion after uniform dispersion;

[0148] (7) Add the dried curing agent to the dispersion, the weight ratio of the dried curing agent to the dispersion is 28:100, and then vacuum stir (temperature is 30°C, vacuum degree is -1.0×10 5 Pa, rotation speed of 3000rmp, time of 30min) to obtain composite coating A5.

[0149] Example 6

[0150] (1) placing epoxy resin (E51), carboxyl-terminated liquid nitrile rubber, diluent (xylene), polyurethane prepolymer (polyether polyurethane) with a number average molecular weight of 500,000, hydrophobic material (graphene with 20 to 60 layers and SiO2 with an average particle size of 80 nm), hydrogen barrier material (SiC with an average particle size of 50 nm and Al2O3 with an average particle size of 50 nm) and curing agent (polyamide and triethylenetetramine) in a vacuum oven and drying at 90°C for 150 min;

[0151] (2) adding the dried hydrophobic material to methanol and silane coupling agent A (KH550), wherein the ratio of the dried hydrophobic material, methanol, water and silane coupling agent A is 1 g: 25 mL: 8 mL: 4.5 mL, stirring for 1 hour, and then filtering, and drying the obtained solid to obtain a silane coupling agent modified hydrophobic material;

[0152] (3) adding the dried hydrogen barrier material to methanol and silane coupling agent B (KH560), wherein the ratio of the dried hydrogen barrier material, methanol, water and silane coupling agent B is 1 g: 24 mL: 6 mL: 5.5 mL, and then filtering and drying the obtained solid to obtain a silane coupling agent modified hydrogen barrier material;

[0153] (4) Add the dried epoxy resin to the dried carboxyl-terminated liquid nitrile rubber and stir under vacuum (temperature 40°C, vacuum degree -0.6×10 5 Pa, speed 450rmp, time 35min), then add the dried diluent, mix well to obtain solution A; add solution A to the dried polyurethane prepolymer, and perform vacuum stirring (temperature 30°C, vacuum degree -1.0×10 5 Pa, a speed of 500rmp, and a time of 30min) to obtain a mixed solution; wherein the total amount of the dried epoxy resin, the dried carboxyl-terminated liquid nitrile rubber and the dried polyurethane prepolymer is 100% by weight, the content of the dried polyurethane prepolymer is 10% by weight, the content of the dried carboxyl-terminated liquid nitrile rubber is 10% by weight, and the content of the dried epoxy resin is 80% by weight; wherein the weight ratio of the amount of the dried diluent to the total amount of the dried epoxy resin, the dried carboxyl-terminated liquid nitrile rubber and the dried polyurethane prepolymer is 80:100;

[0154] (5) Adding a silane coupling agent modified hydrophobic material to the mixed solution, the weight ratio of the silane coupling agent modified hydrophobic material to the mixed solution is 10:100 (wherein the weight ratio of the silane coupling agent modified graphene to the mixed solution is 5:100, and the weight ratio of the silane coupling agent modified SiO2 to the mixed solution is 5:100), and then vacuum stirring is performed (temperature is 30°C, vacuum degree is -1.0×10 5 Pa, speed 300rmp, time 30min);

[0155] (6) Adding a silane coupling agent modified hydrogen barrier material to the material obtained in step (5), wherein the weight ratio of the amount of the silane coupling agent modified hydrogen barrier material to the amount of the mixed solution is 10:100 (wherein the weight ratio of the amount of the silane coupling agent modified SiC to the amount of the mixed solution is 5:100, and the weight ratio of the amount of the silane coupling agent modified Al2O3 to the amount of the mixed solution is 5:100), and then vacuum stirring (temperature is 30°C, vacuum degree is -1.0×10 5 Pa, speed of 5000rmp, time of 30min), and obtain a dispersion after uniform dispersion;

[0156] (7) Add the dried curing agent to the dispersion, the weight ratio of the dried curing agent to the dispersion is 30:100, and then vacuum stir (temperature 30°C, vacuum degree -1.0×10 5 Pa, rotation speed of 3000rmp, time of 30min) to obtain composite coating A6.

[0157] Example 7

[0158] The method of Example 6 is followed, except that the number average molecular weight of the polyurethane prepolymer is 150,000, the average particle size of SiO2 in the hydrophobic material is 100 nm, the average particle size of Al2O3 in the hydrogen barrier material is 1 μm, and in step (4), the weight ratio of the amount of the dried diluent to the total amount of the dried epoxy resin, the dried terminal carboxyl liquid nitrile rubber and the dried polyurethane prepolymer is 30:100; and a composite coating A7 is obtained.

[0159] Example 8

[0160] (1) placing epoxy resin (E51), carboxyl-terminated liquid nitrile rubber, diluent (xylene), polyurethane prepolymer (polyester polyurethane) with a number average molecular weight of 150,000, hydrophobic material (graphene with 20 to 60 layers and SiO2 with an average particle size of 100 nm), hydrogen barrier material (SiC with a particle size of 50 nm and Al2O3 with a particle size of 50 nm) and curing agent (polyamide and triethylenetetramine) in a vacuum oven and drying at 80°C for 80 min;

[0161] (2) adding the dried hydrophobic material to methanol and a silane coupling agent (KH560), wherein the ratio of the dried hydrophobic material, methanol, water and silane coupling agent A is 1 g: 20 mL: 5 mL: 1.25 mL, stirring for 1 h, and then filtering, and drying the obtained solid to obtain a silane coupling agent-modified hydrophobic material;

[0162] (3) adding the dried hydrogen barrier material to methanol and silane coupling agent (KH560), wherein the ratio of the dried hydrogen barrier material, methanol, water and silane coupling agent B is 1 g: 40 mL: 10 mL: 2.5 mL, stirring for 1 h, then filtering, and drying the obtained solid to obtain a silane coupling agent modified hydrogen barrier material;

[0163] (4) Add the dried epoxy resin to the dried carboxyl-terminated liquid nitrile rubber and stir under vacuum (temperature 70°C, vacuum degree -1.0×10 5 Pa, speed 550rmp, time 30min), then add the dried diluent, mix well to obtain solution A; add solution A to the dried polyurethane prepolymer, and stir under vacuum (temperature 30°C, vacuum degree -1.0×10 5 Pa, a speed of 500rmp, and a time of 30min) to obtain a mixed solution; wherein the total amount of the dried epoxy resin, the dried carboxyl-terminated liquid nitrile rubber and the dried polyurethane prepolymer is 100% by weight, the content of the dried polyurethane prepolymer is 10% by weight, the content of the dried carboxyl-terminated liquid nitrile rubber is 20% by weight, and the content of the dried epoxy resin is 70% by weight; wherein the weight ratio of the amount of the dried diluent to the total amount of the dried epoxy resin, the dried carboxyl-terminated liquid nitrile rubber and the dried polyurethane prepolymer is 30:100;

[0164] (5) Adding a silane coupling agent modified hydrophobic material to the mixed solution, the weight ratio of the silane coupling agent modified hydrophobic material to the mixed solution is 10:100 (the weight ratio of the silane coupling agent modified graphene to the mixed solution is 6:100, and the weight ratio of the silane coupling agent modified SiO2 to the mixed solution is 4:100), and then vacuum stirring is performed (the temperature is 30°C, the vacuum degree is -1.0×10 5 Pa, speed 300rmp, time 30min);

[0165] (6) Adding a silane coupling agent modified hydrogen barrier material to the material obtained in step (5), the weight ratio of the amount of the silane coupling agent modified hydrogen barrier material to the amount of the mixed solution is 10:100 (wherein the weight ratio of the amount of the silane coupling agent modified SiC to the amount of the mixed solution is 5:100, and the weight ratio of the amount of the silane coupling agent modified Al2O3 to the amount of the mixed solution is 5:100), and then vacuum stirring (temperature is 30°C, vacuum degree is -1.0×10 5 Pa, speed of 4000rmp, time of 30min), and obtain a dispersion after uniform dispersion;

[0166] (7) Add the dried curing agent to the dispersion, the weight ratio of the dried curing agent to the dispersion is 35:100, and then vacuum stir (temperature is 30°C, vacuum degree is -1.0×10 5 Pa, rotation speed of 3000rmp, time of 30min), and then the composite coating A8 was obtained.

[0167] Example 9

[0168] The method of Example 8 is followed, except that the average particle size of SiO2 in the hydrophobic material is 50 nm, the number of graphene layers is 30-50 layers, and in step (5), the weight ratio of the amount of silane coupling agent modified hydrophobic material to the amount of the mixed liquid is 10:100 (the weight ratio of the amount of silane coupling agent modified graphene to the amount of the mixed liquid is 4:100, and the weight ratio of the amount of silane coupling agent modified SiO2 to the amount of the mixed liquid is 6:100), to obtain a composite coating A9.

[0169] Example 10

[0170] The method of Example 3 is followed, except that the average particle size of SiO2 in the hydrophobic material is 50 nm, the number of graphene layers is 15-70, and in step (4), the weight ratio of the amount of the dried diluent to the total amount of the dried epoxy resin, the dried carboxyl-terminated liquid nitrile rubber and the dried polyurethane prepolymer is 40:100; and a composite coating A10 is obtained.

[0171] Embodiment 11

[0172] The method of Example 3 is followed, except that the number average molecular weight of the polyurethane prepolymer is 300,000, and in step (4), the weight ratio of the amount of the dried diluent to the total amount of the dried epoxy resin, the dried carboxyl-terminated liquid nitrile rubber and the dried polyurethane prepolymer is 20:100; a composite coating A11 is obtained.

[0173] Example 12

[0174] (1) placing epoxy resin (E51), carboxyl-terminated liquid nitrile rubber, diluent (xylene), polyurethane prepolymer (polyester polyurethane) with a number average molecular weight of 500,000, hydrophobic material (graphene with 30 to 70 layers and SiO2 with an average particle size of 50 nm), hydrogen barrier material (SiC with an average particle size of 50 nm and Al2O3 with an average particle size of 100 nm) and curing agent (polyamide and triethylenetetramine) in a vacuum oven and drying at 55°C for 105 min;

[0175] (2) adding the dried hydrophobic material to methanol and a silane coupling agent (KH560), wherein the ratio of the dried hydrophobic material, methanol, water and silane coupling agent A is 1 g: 28 mL: 11 mL: 5 mL, stirring for 1 h, stirring, and then filtering, and drying the obtained solid to obtain a silane coupling agent modified hydrophobic material;

[0176] (3) adding the dried hydrogen barrier material to methanol and silane coupling agent (KH550), wherein the ratio of the dried hydrogen barrier material, methanol, water and silane coupling agent B is 1 g: 19 mL: 10 mL: 5 mL, stirring for 1 h, stirring, and then filtering, and drying the obtained solid to obtain a silane coupling agent modified hydrogen barrier material;

[0177] (4) Add the dried epoxy resin to the dried carboxyl-terminated liquid nitrile rubber and stir under vacuum (temperature 76°C, vacuum degree -1.0×10 5 Pa, speed 500rmp, time 20min), then add the dried diluent, mix evenly to obtain solution A; add solution A to the dried polyurethane prepolymer, and stir under vacuum (temperature 30°C, vacuum degree -1.0×10 5Pa, a speed of 500rmp, and a time of 30min) to obtain a mixed solution; wherein the total amount of the dried epoxy resin, the dried carboxyl-terminated liquid nitrile rubber and the dried polyurethane prepolymer is 100% by weight, the content of the dried polyurethane prepolymer is 65% by weight, the content of the dried carboxyl-terminated liquid nitrile rubber is 10% by weight, and the content of the dried epoxy resin is 25% by weight; wherein the weight ratio of the amount of the dried diluent to the total amount of the dried epoxy resin, the dried carboxyl-terminated liquid nitrile rubber and the dried polyurethane prepolymer is 40:100;

[0178] (5) Adding a silane coupling agent modified hydrophobic material to the mixed solution, the weight ratio of the silane coupling agent modified hydrophobic material to the mixed solution is 10:100 (wherein the weight ratio of the silane coupling agent modified graphene to the mixed solution is 5:100, and the weight ratio of the silane coupling agent modified SiO2 to the mixed solution is 5:100), and then vacuum stirring is performed (temperature is 30°C, vacuum degree is -1.0×10 5 Pa, speed 300rmp, time 30min);

[0179] (6) Adding a silane coupling agent modified hydrogen barrier material to the material obtained in step (5), the weight ratio of the amount of the silane coupling agent modified hydrogen barrier material to the amount of the mixed solution is 10:100 (the weight ratio of the amount of the silane coupling agent modified SiC to the amount of the mixed solution is 2:100, and the weight ratio of the amount of the silane coupling agent modified Al2O3 to the amount of the mixed solution is 8:100), and then vacuum stirring is performed (the temperature is 30°C, the vacuum degree is -1.0×10 5 Pa, speed of 5000rmp, time of 30min), and obtain a dispersion after uniform dispersion;

[0180] (7) Add the dried curing agent to the dispersion, the weight ratio of the dried curing agent to the dispersion is 35:100, and then vacuum stir (temperature is 30°C, vacuum degree is -1.0×10 5 Pa, rotation speed of 3000rmp, time of 30min) to obtain a composite coating A12.

[0181] Comparative Example 1

[0182] In this comparative example, no carboxyl-terminated liquid nitrile rubber, polyurethane prepolymer, diluent, hydrophobic material and hydrogen barrier material are used, and epoxy resin and curing agent are directly used as raw materials to prepare epoxy resin hydrogen barrier coating D1. The specific preparation method is as follows:

[0183] (1) The epoxy resin (E51) and the curing agent (triethylenetetramine and polyamide) were placed in a vacuum oven and dried at 70°C for 80 min;

[0184] (2) Add the dried curing agent to the dried epoxy resin (the weight ratio of the dried curing agent to the dried epoxy resin is 25:100) and stir under vacuum (temperature is 60°C, vacuum degree is -1.0×10 5 Pa, speed of 600 rpm, time of 30 min), and after mixing evenly, the epoxy resin hydrogen barrier coating D1 was obtained.

[0185] Comparative Example 2

[0186] The method of Example 1 is used, except that no hydrophobic material and hydrogen barrier material are used. The specific operation is as follows:

[0187] (1) placing epoxy resin (E51), carboxyl-terminated liquid nitrile rubber, diluent (xylene), polyurethane prepolymer (polyether polyurethane) with a number average molecular weight of 10,000, and curing agent (polyamide) in a vacuum oven and drying at 70° C. for 80 min;

[0188] (2) Add the dried epoxy resin to the dried carboxyl-terminated liquid nitrile rubber and stir under vacuum (temperature 50°C, vacuum degree -1.0×10 5 Pa, speed of 500 rpm, time of 20 min), then add the dried diluent, mix well to obtain solution A; add solution A to the dried polyurethane prepolymer, and perform vacuum stirring (temperature of 30°C, vacuum degree of -1.0×10 5 Pa, a speed of 500rmp, and a time of 30min) to obtain a mixed solution; wherein the total amount of the dried epoxy resin, the dried carboxyl-terminated liquid nitrile rubber and the dried polyurethane prepolymer is 100% by weight, the content of the dried polyurethane prepolymer is 5% by weight, the content of the dried carboxyl-terminated liquid nitrile rubber is 10% by weight, and the content of the dried epoxy resin is 85% by weight; wherein the weight ratio of the amount of the dried diluent to the total amount of the dried epoxy resin, the dried carboxyl-terminated liquid nitrile rubber and the dried polyurethane prepolymer is 30:100;

[0189] (3) Add the dried curing agent to the mixed solution, the weight ratio of the dried curing agent to the dispersion is 5:100, and then vacuum stir (temperature is 30°C, vacuum degree is -1.0×10 5 Pa, rotation speed of 3000rmp, time of 30min) to obtain a composite coating D2.

[0190] Comparative Example 3

[0191] The method of Example 1 is implemented, except that no carboxyl-terminated liquid nitrile rubber is used. That is, in step (4), the dried epoxy resin is added to the dried diluent, and the mixture is mixed to obtain solution A; solution A is added to the dried polyurethane prepolymer and vacuum stirred (temperature is 30°C, vacuum degree is -1.0×10 5 Pa, speed of 500rmp, time of 30min), to obtain a mixed liquid; wherein the total amount of the dried epoxy resin and the dried polyurethane prepolymer is 100wt%, the content of the dried polyurethane prepolymer is 10wt%, and the content of the dried epoxy resin is 90wt%; wherein the weight ratio of the amount of the dried diluent to the total amount of the dried epoxy resin and the dried polyurethane prepolymer is 30:100; to obtain a composite coating D3.

[0192] Test Example 1

[0193] The composite coatings A1-A12 and D1-D3 were respectively evenly coated on 316 steel sheets of size 3cm×3cm, and placed at room temperature (25°C) to cure and form coatings of the same thickness. Hydrogen diffusion experiments were carried out on the obtained coatings using a Devnathan-Stachurski double electrolytic cell to obtain the hydrogen permeation current and the range of variation of the hydrogen permeation current density.

[0194] The detection method is as follows: first, after fixing the coating sample, the anode pool solution is configured with a 0.2 mol / L NaOH solution, and the cathode pool solution is configured with a 3.5% NaCl solution. The reference electrode type of the main channel is Hg / HgO (1M NaOH), and the reference electrode of the secondary channel is SCE (mercury / calomel saturated KCL). The results are shown in Table 1.

[0195] Table 1

[0196]

[0197]

[0198] It can be seen from the results in Table 1 that the coating formed by the composite coating obtained in the embodiment of the present invention has a lower hydrogen permeation current density, and the smaller the hydrogen permeation current density, the lower the hydrogen permeability and the stronger the hydrogen permeation resistance, indicating that the high cross-linking density ternary interpenetrating network structure formed by grafting in the present invention can significantly improve the hydrogen permeation resistance of the coating substrate material; the cross-linking density of the material is increased by compounding the micro-nano scale functional filler and its mutual chemical reaction with the ternary interpenetrating matrix, the hydrogen transmission path is extended, and a significant hydrogen barrier effect is played. The formed composite coating has the advantages of simple preparation and significant hydrogen barrier effect, and can be widely used in the coating and protection of any hydrogen-prone metal surface.

[0199] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A composite coating, characterized in that: The raw materials for preparing the composite coating contain epoxy resin, carboxyl-terminated liquid nitrile rubber, polyurethane prepolymer, hydrophobic material and hydrogen barrier material.

2. The composite coating according to claim 1, characterized in that: The hydrogen permeation current density of the composite coating is 0.1-0.28 μA / cm 2 .

3. The composite coating according to claim 1 or 2, characterized in that: The hydrophobic material is SiO2 and / or graphene; Preferably, the average particle size of the SiO2 is 50-800nm; Preferably, the number of graphene layers is 5-70.

4. The composite coating according to claim 1 or 2, characterized in that: The hydrogen barrier material is one or more of Al2O3, SiC and Ti3C2 nanosheets; Preferably, the average particle size of Al2O3 is 20nm-1μm; Preferably, the average particle size of the SiC is 50-800 nm; Preferably, the number of layers of the Ti3C2 nanosheets is 8-40.

5. The composite coating according to claim 1, characterized in that: The epoxy resin is selected from E51 and / or E44; Preferably, the number average molecular weight of the polyurethane prepolymer is 10000-500000; Preferably, the polyurethane prepolymer is polyether polyurethane and / or polyester polyurethane.

6. The composite coating according to claim 1, characterized in that: The raw materials for preparing the composite coating also contain auxiliary agents; Preferably, the auxiliary agent contains a curing agent and a diluent; Preferably, the diluent is selected from one or more of xylene, n-butanol and dimethylformamide; Preferably, the curing agent is one or more of polyamide, triethylenetetramine and 3,3'-dichloro-4,4'-diaminodiphenylmethane.

7. A method for preparing a composite coating, characterized in that: The method comprises the following steps: (1) mixing epoxy resin, carboxyl-terminated liquid nitrile rubber, a diluent and a polyurethane prepolymer to obtain a mixed solution; (2) mixing a hydrophobic material, a hydrogen barrier material and the mixed liquid to obtain a dispersion; (3) Mixing the dispersion and the curing agent.

8. The method according to claim 7, characterized in that The specific steps of step (1) include: (a) an epoxy resin and a carboxyl-terminated liquid nitrile rubber are subjected to vacuum stirring and then mixed with a diluent to obtain a solution A; (b) vacuum stirring the polyurethane prepolymer and the solution A to obtain a mixed solution.

9. The method according to claim 7 or 8, characterized in that: Taking the total amount of epoxy resin, carboxyl-terminated liquid nitrile rubber and polyurethane prepolymer as 100 weight %, the amount of polyurethane prepolymer is 5-80 weight %, the amount of carboxyl-terminated liquid nitrile rubber is 10-70 weight %, and the amount of epoxy resin is 10-85 weight %.

10. The method according to claim 7 or 8, characterized in that: The weight ratio of the amount of the diluent to the total amount of the epoxy resin, the carboxyl-terminated liquid nitrile rubber and the polyurethane prepolymer is 10-80:

100.

11. The method according to claim 7 or 8, characterized in that: In step (a), the vacuum stirring conditions include: temperature of 30-120°C, vacuum degree of -0.5×10 5 Pa~-1×10 5 Pa, speed 400-600rmp, time 20-40min; Preferably, in step (b), the vacuum stirring conditions include: a temperature of 30-120°C, a vacuum degree of -0.5×10 5 Pa~-1×10 5 Pa, speed is 400-600rmp, time is 20-40min.

12. The method according to claim 7, characterized in that The specific steps of step (2) include: S1, vacuum stirring the hydrophobic material and the mixed solution; S2. The material obtained in step S1 and the hydrogen barrier material are vacuum stirred to obtain a dispersion.

13. The method according to claim 7 or 12, characterized in that: The weight ratio of the amount of the hydrophobic material to the amount of the mixed solution is 1-10:100; Preferably, the weight ratio of the amount of the hydrogen barrier material to the amount of the mixed liquid is 1-15:

100.

14. The method according to claim 7 or 12, characterized in that: In step S1, the vacuum stirring conditions include: temperature of 30-120°C, vacuum degree of -0.5×10 5 Pa~-1×10 5 Pa, speed 100-1000rmp, time 20-40min; Preferably, in step S2, the vacuum stirring conditions include: a temperature of 30-120°C, a vacuum degree of -0.5×10 5 Pa~-1×10 5 Pa, speed is 3000-5000rmp, time is 20-40min.

15. The method according to claim 7, characterized in that In step (3), the weight ratio of the amount of the curing agent to the amount of the dispersion is 5-50:

100.

16. The method according to claim 7 or 15, characterized in that In step (3), the mixing operation is vacuum stirring; Preferably, the vacuum stirring conditions include: temperature of 30-120°C, vacuum degree of -0.5×10 5 Pa~-1×10 5 Pa, speed is 3000-5000rmp, time is 20-40min.

17. Use of the composite coating according to any one of claims 1 to 6 or the composite coating obtained by the method for preparing the composite coating according to any one of claims 7 to 16 in hydrogen embrittlement protection of metal materials.

Citation Information

Patent Citations

  • Anti-hydrogen corrosion-resistant coating and preparation method

    CN107916045A

  • Modified epoxy resin and preparation method thereof, epoxy resin coating and preparation method and application thereof

    CN115181276A

  • Solvent-free epoxy primer for high temperature corrosion prevention of steel pipeline welded junction position

    CN102382553A

  • Polymer film material with hydrogen absorption function and preparation method thereof

    CN112341822A

  • Organic hydrogen permeation-resistant coating as well as preparation method and application thereof

    CN115093769A

Cited By

  • Modified nitrile rubber seal material resistant to hydrogen permeation damage and method of making

    CN122628408A